1995
DOI: 10.1001/archpsyc.1995.03950240066012
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder in the National Comorbidity Survey

Abstract: Posttraumatic stress disorder is more prevalent than previously believed, and is often persistent. Progress in estimating age-at-onset distributions, cohort effects, and the conditional probabilities of PTSD from different types of trauma will require future epidemiologic studies to assess PTSD for all lifetime traumas rather than for only a small number of retrospectively reported "most serious" traumas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

519
6,654
114
287

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9,068 publications
(7,574 citation statements)
references
References 39 publications
519
6,654
114
287
Order By: Relevance
“…However, roughly a quarter to a half of VTE cases, overall, are classified as occurring in the absence of major established risk factors,6 thus emphasizing the need for greater understanding of susceptibility to VTE. PTSD is twice as common in women as in men,11 and our findings suggest that elevated PTSD symptoms (over and above the effects of trauma type and depression, a psychological disorder that is frequently comorbid with PTSD and has also been linked with risk of VTE9, 10) may be an important vulnerability factor for developing VTE in women. Given that VTE is a leading cause of mortality among pregnant and recently postpartum women,3 and in light of female‐specific risk factors for VTE related to reproductive hormone exposure,3 pregnant women with PTSD symptoms or women with PTSD symptoms who are using hormone therapy may represent especially vulnerable groups with respect to VTE risk.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, roughly a quarter to a half of VTE cases, overall, are classified as occurring in the absence of major established risk factors,6 thus emphasizing the need for greater understanding of susceptibility to VTE. PTSD is twice as common in women as in men,11 and our findings suggest that elevated PTSD symptoms (over and above the effects of trauma type and depression, a psychological disorder that is frequently comorbid with PTSD and has also been linked with risk of VTE9, 10) may be an important vulnerability factor for developing VTE in women. Given that VTE is a leading cause of mortality among pregnant and recently postpartum women,3 and in light of female‐specific risk factors for VTE related to reproductive hormone exposure,3 pregnant women with PTSD symptoms or women with PTSD symptoms who are using hormone therapy may represent especially vulnerable groups with respect to VTE risk.…”
Section: Discussionmentioning
confidence: 65%
“…Growing evidence suggests that psychosocial factors, such as depression, which have been linked to cardiovascular risk more broadly, are also associated with VTE risk in particular 9, 10. The majority of individuals in the general population (at least 60% according to most studies11, 12) are exposed to 1 or more traumatic events (eg, sexual assault, physical assault, combat, natural disasters) during their lifetime. Posttraumatic stress disorder (PTSD) is a psychological consequence of exposure to such traumatic events, and is characterized by symptoms of re‐experiencing of the trauma, avoidance of trauma reminders, negative alterations in mood and thinking, and hyperarousal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifetime prevalence is estimated at 1.3–12.2% (Karam et al, 2014). The probability of developing PTSD after a traumatic event varies according several risk factors (Hoge, Riviere, Wilk, Herrell, & Weathers, 2014, Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995) which can be classified as pre-trauma (sex, IQ, prior trauma exposure, prior mental disorder, genetics, personality factors), related to trauma (perceived fear of death, assaultive trauma, severity of trauma, physical injury) or post-trauma (high heart rate, low social support, financial stress, pain severity, intensive care stay, traumatic brain injury, peritraumatic dissociation, acute stress disorder, disability; Sareen, 2014). Functional and emotional impairments impact on quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that traumatic losses in this group can lead to both PCBD and PTSD (Momartin, Silove, Manicavasagar, & Steel, 2004; Nickerson et al, 2014; Stammel et al, 2013). Comorbidity of PCBD and/or PTSD with other psychiatric disorders such as major depressive disorder (MDD) (Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995; Schaal, Dusingizemungu, Jacob, Neuner, & Elbert, 2012), psychotic disorders (Sareen, Cox, Goodwin, & Asmundson, 2005) and substance abuse disorders (Kessler et al, 1995) is often observed. Furthermore, refugees are confronted with ongoing stressors that can fuel the risk for psychopathology (Laban 2004, 2005), such as insecurity about residential status, concerns about wellbeing of family members left behind, socioeconomic disadvantage, and adaptation to the host culture.…”
mentioning
confidence: 99%